Research progress of superhydrophobic coatings based on silicone rubber surface. Issue 1 (1st November 2022) - Xie, X W; Zhao, Y J; Shi, J B
Abstract : Silicone rubber has excellent insulation properties such as good hydrophobic mobility and anti pollution flashover performance. It plays an important role in the power system and provides an important guarantee for the reliability of power supply. However, due to the erosion of various harsh environments, especially in wet environments such as rain and snow, a large amount of dirt and water are easily attached to the surface of insulating parts. It not only reduces its surface hydrophobicity and hydrophobic mobility, but also greatly shortens its service life. There are even serious leakage current problems. Especially in the low temperature environment, a lot of snow and flashover will occur at the accessories of the insulation parts. In order to solve this problem, super hydrophobic self-cleaning coating based on silicone rubber surface came into being. The preparation principle and model of superhydrophobic self-cleaning coating on silicone rubber surface are reviewed in this paper. By comparing different preparation methods, the advantages, disadvantages and application prospects are analyzed, and the existing problems and challenges are put forward according to the existing preparation technologies, so as to lay a theoretical foundation for preparing self-cleaning coatings with excellent performance in the future.